2003
DOI: 10.1088/0953-4075/36/6/101
|View full text |Cite
|
Sign up to set email alerts
|

Strongly directed electron emission in non-sequential double ionization of Ne by intense laser pulses

Abstract: Double ionization of Ne by 25 fs, 1.0 PW/cm 2 laser pulses has been explored in a kinematically complete experiment using a "Reaction Microscope".Electrons are found to be emitted into a narrow cone along the laser polarization (ε), much more confined than for single ionization, with a broad maximum in their energy distribution along ε. Correlated momentum spectra show both electrons being ejected into the same hemisphere, in sharp contradiction to predictions based on field-free (e,2e) recollision dynamics, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 26 publications
(46 reference statements)
6
36
0
Order By: Relevance
“…Figure 4 displays the first experiment of this kind, which employed argon [32]; see also [33]. Corresponding results for neon can be found in [34]. We observe that the momentum correlation is concentrated in the first and the third quadrants implying that the electrons are predominantly leaving the laser focus side by side.…”
Section: Ion-momentum Distributions and Electron-electron Momentum Comentioning
confidence: 59%
“…Figure 4 displays the first experiment of this kind, which employed argon [32]; see also [33]. Corresponding results for neon can be found in [34]. We observe that the momentum correlation is concentrated in the first and the third quadrants implying that the electrons are predominantly leaving the laser focus side by side.…”
Section: Ion-momentum Distributions and Electron-electron Momentum Comentioning
confidence: 59%
“…addition to explaining the observed above-threshold ionization (ATI) and high harmonic generation (HHG) spectra, also well accounted for NSDI. The evidence in support of the rescattering mechanism accumulated over the years to include experiments on ellipticity dependence of NSDI [4][5][6], ATI [7] and HHG [8,9], ion recoil momentum distributions [10][11][12][13], correlated two-electron momentum distributions [14]a n d molecular clocks [15,16]. It was also shown experimentally that shake-off/shake-up does not play an important role [17].…”
Section: +mentioning
confidence: 98%
“…The latter step most likely occurs near one of the field maxima, resulting in small ion drift momenta and, thus, in a 'filling of the valley' in the momentum distributions. Estimations of the cross sections for collision-induced ionization/excitation [9] as well as the analysis of correlated electron momenta [10][11][12] showed that RESI plays a decisive role for He and Ar, whereas for Ne recollision induced electron-impact ionization clearly dominates.…”
mentioning
confidence: 99%